1977
DOI: 10.1002/1097-0142(197704)39:4<1495::aid-cncr2820390422>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Marker chromosome 14q+ in non-endemic Burkitt's lymphoma

Abstract: The chromosomal aberrations in tumor cells obtained by bone marrow aspiration from a patient with non-endemic Burkitt's lymphoma (BL) are reported. Twenty percent of the cells contained the marker chromosome 14q+ earlier described in endemic Burkitt's tumors. Other marker chromosomes were dound only in mitoses which did not contain the 14q+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…14 having at the end of its long arm an additional band, positive in Q-and G-banding. This finding has been confirmed by a number of authors (PETIT et al 1972;JARVIS et al 1974;ZECH et al 1976;KAISER-MCCAW et al 1976PHILIP et al 1977;TEMPLE le77). Markers more or less similar to the original marl4q+ have also been demonstrated in other types of lymphoid neoplasia (REEVES 1973;MARK 1975;PHILIP 1975;PRIGOGINA and FLEISCHMAN 1975;FLEISCHMAN and PRK;OGINA 1977;LUNG and ROWLEY 1978).…”
supporting
confidence: 52%
“…14 having at the end of its long arm an additional band, positive in Q-and G-banding. This finding has been confirmed by a number of authors (PETIT et al 1972;JARVIS et al 1974;ZECH et al 1976;KAISER-MCCAW et al 1976PHILIP et al 1977;TEMPLE le77). Markers more or less similar to the original marl4q+ have also been demonstrated in other types of lymphoid neoplasia (REEVES 1973;MARK 1975;PHILIP 1975;PRIGOGINA and FLEISCHMAN 1975;FLEISCHMAN and PRK;OGINA 1977;LUNG and ROWLEY 1978).…”
supporting
confidence: 52%
“…Outside Africa, Burkitt type ALL has been reported to represent 2 % of all ALL . In African (Manolov and Manolova, 1972) and non-African (Hubner and Littlefield, 1975;Philip et al, 1977) Burkitt ML, structural chromosomal abnormalities were found. The existence of ML in which a variable proportion of the neoplastic cells show mature or immature plasmacytic or plasmacytoid features is fully recognised.…”
Section: Malignant Lymphomas Made Up Exclusively Ormentioning
confidence: 98%
“…The 14q+ marker chromosome, first desc:ibed by Manolov and Manolova (1972) has been confirmed as a characteristic and consistent finding in Burkitt's lymphoma (BL) (references in Mitelman and Levan, 1978). The marker has been found in all of the tumor biopsies studied not only from Africa but also from the USA (Kaiser-McCaw et al, 1977) and Europe (Philip et al, 1977). Zech el al.…”
Section: Discussionmentioning
confidence: 93%